NEW ANTIPLATELET DRUGS (PART 1) - A. B. Sumarokov (Столичная издательская компания, 2016)
Antiplatelet agents are a necessary component of modern atherosclerosis therapy. The difficulties of antiplatelet treatment lie in the balance between the necessary therapeutic effect of the drug and the risk of excessive action leading to the bleeding. Possibility to control pharmacodynamics effects of antiplatelet agents is still very limited. Pharmacology of antiplatelet drugs is growing rapidly. Some of new antiplatelet drugs are on their way to clinical application - prasugrel, ticagrelor, elinogrel, inhibitors of thromboxane and thrombin receptors. Clinical pharmacology of these drugs is different. This requires a doctor's good knowledge of their identity to avoid the development of iatrogenic complications.